Green Synthesis, Characterization, Cytotoxicity Studies of Alumina Nanoparticles Using Carica Papaya and Evaluation for Their Potential Antibacterial Properties - Bukar, Alhaji Modu; Mustapha, Babagana; Jesse, Faez Firdaus Abdullah; Abdullah, Che Azurahanim Che; Noordin, Mustapha M.; Kyari, Modu Z.; Shettima, Fatima Bukar; Norman, Ashreen; Lila, Mohd Azmi Mohd (Yayasan Gema Bina Nusantara, 2024)
The environmentally friendly synthesis, characterization, evaluation of potential toxicity and antibacterial development of alumina nanoparticles (Al2O3NPs) has become one of the best approaches to address the problem of antimicrobial drug resistance. The recent advances in the field of nanotechnology have thus made a great contribution to medical, biomedical, pharmaceutical and drug discovery research. Moreover, the tiny Al2O3NPs have a great success in inhibiting various types of microbes that cause diseases in humans and animals. In this study, we use the simplest, cheapest, less time-consuming and most effective green synthesis approach to produce environmentally friendly Al2O3NPs. In this study, the Al2O3NPs were synthesized from Carica papaya leaf extract (CPL) and examined microscopically for their size and shape. Fourier transform infrared spectroscopy (FTIR) was performed to determine the concentration of metal ions and the shape of the molecules. In vitro cytotoxicity was performed on different mammalian cell lines to determine the safety of the Al2O3NPs. Finally, bactericidal activity was evaluated using the agar plug diffusion method. The result showed 50–60 nm sized spherical nanoparticles. Turbidity analysis revealed MIC and MBC of >25 μg/mL against both Gram-positive and Gram-negative bacteria on Mueller-Hilton agar cultures. In conclusion, the Al2O3NPs synthesized from CPL exhibited acceptable nanoparticle size and shape as well as effective bactericidal activity.